Spectrofluorimetric Method for Simultaneous Determination of Trimethoprim and Sulfamethoxazole with O-phthaladehyde Reagent by H-point Standard Addition Method - Alsayegh, Amneen Mohammed; Alshirifi, Abbas Noor (Indonesian Journal of Chemistry, 2024)
Simultaneous spectrofluorometric method described for the determination of trimethoprim (TMP) and sulfamethoxazole (SMZ) in pure and pharmaceutical preparations using H-point standard addition method (HPSAM) according to the reaction of nanograms of drugs with O-phthaladehyde (OPA) reagent to forms highly fluorescence compounds. The formed fluorophore excitation and emission at 342 and 458 nm, respectively, for OPA-TMP compound, at 424 and 508 nm, respectively, for OPA-SMZ compound under basic condition (pH 9.8) in the presence of 2-mercabtoethanol. A simple and accurate HPSAM is reported to resolve the overlapping in the fluorescence spectrum of these two drugs without prior separation of samples. The linear range was 100–1200 ng/mL for TMP and 100–1100 ng/mL for SMZ. The LOD and LOQ were 16.64 and 36.80 ng/mL, as well as 15.76 and 33.88 ng/mL for TMP and SMZ, respectively. The relative standard deviations and recovery percentages were 0.641% and 101.29% for TMP as well as 0.558% and 100.96% for SMZ, respectively. The procedure has been applied successfully in various pharmaceutical preparations. It was discovered that the experimental F- and t-values at a 95% confidence level were no higher than the theoretical values, showing that the HPSAM method is accurate and valid.